Nutritional value, bioactive compounds, antimicrobial activity and bioaccessibility studies with wild edible mushrooms - Heleno, Sandrina A. (2015)
Wild mushrooms are important sources of nutrients and bioactive compounds, namely phenolic acids. After their ingestion, bioactive molecules have to be released from the matrix to be absorbed by the organism. In the present work, two wild edible mushrooms (Volvopluteus gloiocephalus and Clitocybe subconnexa) were studied for their nutritional value, detailed chemical composition and antimicrobial activity. Bioacessibility studies were also performed using the in vitro digestion of the crude powder, phenolic extracts and individual phenolic acids identified in the samples. The studied species proved to be rich sources of nutrients, minerals and bioactive molecules such as phenolic acids. The in vitro digestion conducted to a decrease in antibacterial activity, but not in antifungal and demelanizing properties. Nevertheless, in most of the cases, the analyzed samples presented higher antibacterial and antifungal activities than the standards. The bioactive molecules (phenolic acids) were found in higher concentrations in the phenolic extracts before in vitro digestion, which is agreement with the highest antibacterial activity revealed by these extracts. It should be highlighted that the phenolic acids were still bioavailable after digestion.